2011
DOI: 10.1186/1748-717x-6-74
|View full text |Cite
|
Sign up to set email alerts
|

Sparing the contralateral submandibular gland without compromising PTV coverage by using volumetric modulated arc therapy

Abstract: BackgroundSalivary gland function decreases after radiation doses of 39 Gy or higher. Currently, submandibular glands are not routinely spared. We implemented a technique for sparing contralateral submandibular glands (CLSM) during contralateral elective neck irradiation without compromising PTV coverage.MethodsVolumetric modulated arc therapy (RapidArc™) plans were applied in 31 patients with stage II-IV HNC without contralateral neck metastases, all of whom received elective treatment to contralateral nodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
2
20
0
2
Order By: Relevance
“…OAR planning goals included maximizing point doses to the spinal cord, brainstem, and their planning atrisk volumes (3-mm expansion), and lowering the mean dose to parotid and submandibular glands (SMGs), individual swallowing muscles, and the oral cavity as much as possible. RapidArc optimization for HNC was performed interactively by continuously adapting the location of the OAR optimization objectives according to our institutional optimization protocol (19)(20)(21). Reduced clinical plan quality could occasionally be obtained if the institutional optimization protocol was not followed thoroughly.…”
Section: Methods and Materials Clinical Plansmentioning
confidence: 99%
“…OAR planning goals included maximizing point doses to the spinal cord, brainstem, and their planning atrisk volumes (3-mm expansion), and lowering the mean dose to parotid and submandibular glands (SMGs), individual swallowing muscles, and the oral cavity as much as possible. RapidArc optimization for HNC was performed interactively by continuously adapting the location of the OAR optimization objectives according to our institutional optimization protocol (19)(20)(21). Reduced clinical plan quality could occasionally be obtained if the institutional optimization protocol was not followed thoroughly.…”
Section: Methods and Materials Clinical Plansmentioning
confidence: 99%
“…It is also important to mention that 14 of the 46 patients that started the study underwent RT treatment with a non-conventional fractionation. This was Simultaneous Integrated Boost (SIB) for clinical orientation, which determines the total time of treatment (there is a um comportamento temporário 5,6 . Na irradiação da região de Cabeça e Pescoço os danos nos tecidos normais tornam-se evidentes, principalmente por se tratar de uma área complexa (RTOG), em casos de complicações graves, ou seja, de aparecimento de efeitos agudos severos ao tratamento, este é interrompido por incapacidade do doente em continuar a terapia, o que afeta diretamente a sobrevida e a própria eficácia da terapia na procura pela cura do doente.…”
Section: Methodsunclassified
“…In comparison, the RapidArc TM technique provoked effects in mucosa only in week 6. Patients from both treatment techniques were also undergoing combined treatment with chemotherapy, which could have influenced the toxicity increase in the normal tissues 10,18,5,6 . With regards to the salivary glands results, we have observed that all IMRT patients demonstrated effects in the 4 th week of treatment, with some patients experiencing high-degree effects.…”
Section: Scorsetti and His Group In 2010 Initiated A Clinical Experimmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advancements, xerostomia remains a regular and morbid toxicity experienced by patients following head and neck radiotherapy. This may result in dysphagia, eating and speaking difficulties, increased risk of dental caries and osteoradionecrosis, and can have a significant impact on the quality of life …”
Section: Introductionmentioning
confidence: 99%